Prevalence of hepatitis B virus infection and its associated factors in Ethiopia: a recent systematic review and meta-analysis - Senait Tadesse; Abaineh Munshea; Baye Gelaw; Norbert Peshu; Endalamaw Tesfa; Feleke Mekonnen; Mulugeta Mihrete Tefera; Getachew Kahsu; Demeke Endalamaw; Anna Kramvis; Meseret Adugna; Steve Wandiga (BMC Infectious Diseases)
Abstract Background Hepatitis B virus (HBV) is one of the most common causes of chronic liver disease and is a growing concern in low-income countries, including Ethiopia. Different studies have been conducted on the prevalence of HBV infection among Ethiopian regions and population segments. Therefore, this systematic review was commenced to summarize these findings, deliver representative pooled data on the prevalence of HBV infection among Ethiopian administrative regions and population segments, and identify possible factors associated with HBV infection. Methods Electronic databases such as PubMed, African Journals Online, and Google Scholar were searched for published articles from July 9, 2019, to February 30, 2024. The data were exported to STATA version 15.1 for meta-analyses. The heterogeneity between the results of the primary studies was accessed using Cochran’s Q chi-square test and quantified with I2 statistics. A random effect model was used to pool the prevalence of HBV infection. Results The overall pooled prevalence of HBV infection was 6.9% (95% CI: 6.1, 7.7). Among the subgroup analyses, the highest pooled prevalence of HBV infection was obtained from Harar city 9.6% (95% CI: 5.6, 13.5), followed by South Nations and Nationalities People Regions (SNNPR) 8.5% (95% CI: 7.4, 9.7). On the other hand, the pooled prevalence of HBV infection among waste handlers was high 12.6% (95% CI: 2.4, 27.6) followed by female commercial sex workers (FCSW) 10.9% (95% CI: 7.7, 15.2) and human immune deficiency virus (HIV) positive individuals 9.9% (95% CI: 7.2, 12.8). HBV infection was significantly linked to the following factors: those with multiple sexual partners, a family history of chronic liver disease, exposure to bodily fluids, HIV seropositivity, and sharp needle injury had Adjusted Odd Ratio (AOR):3.9 (95% CI: 2.62, 5.76), (AOR: 6.9 (95% CI:3.46, 10.53), (AOR:3.1 (95% CI: 2.01, 3.05), (AOR:7.7 (95% CI: 2.99, 19.93), (AOR:2.1 (95% CI: 1.58, 2.66) times a greater chance of infection, respectively. Conclusions The high pooled prevalence of HBV infection in Ethiopia indicates that the burden of HBV infection continues to be a public health concern. The Ethiopian Ministry of Health should develop a strategic plan for prevention and control of HBV infection transmission including awareness creation, scale-up screening programs, diagnosis, treatment, and care services to reduce the burden of HBV infection and eliminate it as a public health threat.